2014
DOI: 10.4314/mejs.v6i2.109714
|View full text |Cite
|
Sign up to set email alerts
|

Status of Lion (<i>Panthera leo</i>) and Spotted Hyena (<i>Crocuta crocuta</i>) in Nechisar National Park, Ethiopia

Abstract: Globally large carnivores are in decline due to a combination of habitat degradation and direct human persecution. A survey was conducted in Nechisar national park, Southern Ethiopia to investigate the population status of lion (Panthera leo) and hyena (Crocuta crocuta). Eleven callups were performed; a total of two adult male lions and six spotted hyenas responded. Estimates give a lion density of between 2 and 5 per 100 km 2 or a total population estimate of 7 to 23 lions and a hyena density of between 4 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
8
3
Order By: Relevance
“…Gandiwa (2012) also reported that local residents wanted a reduction in the population of spotted hyena, serval, and black‐backed jackal. The majority of studies in Ethiopia suggest that local residents are against spotted hyena conservation due to livestock damage (Biset et al, 2019; Yirga et al, 2014; Young et al, 2020). In this study, livestock depredation and crop damage are the major causes of negative attitudes among local people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gandiwa (2012) also reported that local residents wanted a reduction in the population of spotted hyena, serval, and black‐backed jackal. The majority of studies in Ethiopia suggest that local residents are against spotted hyena conservation due to livestock damage (Biset et al, 2019; Yirga et al, 2014; Young et al, 2020). In this study, livestock depredation and crop damage are the major causes of negative attitudes among local people.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on local people's perceptions and attitudes toward carnivore population abundance and trends, as well as conservation, are either scarce or, if available, species‐specific and limited to protected areas. To date, studies on attitudes toward carnivores in Ethiopia have been biased toward the spotted hyena ( Crocuta crocuta ), Ethiopian wolf ( Canis simensis ), and lion ( Panthera leo ) (Gebresenbet, Baraki, et al, 2018; Yirga et al, 2014; Young et al, 2020). Furthermore, the majority of recent wildlife studies have focused on herbivores (Abraham & Simon, 2020; Yosef, 2015), as well as conflicts between humans and wildlife in national parks (Biset et al, 2019; Mekonen, 2020; Merkebu & Yazezew, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yirga et al (2014) reported livestock conflict as the main cause for the decline of large carnivore populations in Nechisar, with Guji herders persecuting large carnivores. Anthropogenic factors are driving the lions in Nechisar to extinction; reportedly any lion that ventures near livestock is pre-emptively shot (Yirga et al 2014). Lions are being systematically killed for preying on livestock in Ethiopia.…”
Section: Lion Abundancementioning
confidence: 99%
“…The same is true in Ethiopia that no quantitative studies have been carried out on carnivores at a community level, but there exist only at the species-specific level [18,20]. For instance, species-specific studies conducted for lion and hyena [21,22], leopard [23], African civet [24,25], mongooses [26], and Ethiopian wolf [27].…”
Section: Introductionmentioning
confidence: 99%